LINC01534 Promotes the Aberrant Metabolic Dysfunction and Inflammation in IL-1β-Simulated Osteoarthritic Chondrocytes by Targeting miR-140-5p. (December 2021) - wei, Wei; He, Shaoxuan; Wang, Zhihua; Dong, Junjie; Xiang, Dong; Li, Yunxuan; Ren, Lirong; Kou, Nannan; Lv, Jia
Objective: Long non-coding RNA 01534 (LINC01534) is highly expressed in the tissues of patients with osteoarthritis (OA). This study investigated the mechanism of LINC01534 on abnormal metabolic dysfunction in OA chondrocytes induced by interleukin-1β (IL-1β). Methods: The quantitative real-time polymerase chain reaction (qRT-PCR) was used to determine the expressions of LINC01534, aggrecan, collagen II, and matrix metalloproteinase (MMPs) in OA cartilage tissue or OA chondrocyte model induced by IL-1β. The expressions of aggrecan and collagen II in the chondrocyte were detected by Western blot. The levels of tumor necrosis factor–α (TNF-α), IL-8, IL-6, MMP-13, MMP-9, MMP-3, and prostaglandin E2 (PGE2) in chondrocyte were determined by enzyme-linked immunosorbernt assay. Bioinformatics, dual luciferin gene reporting, RNA pulldown, and Northern blot were used to determine the interaction between LINC01534 and miR-140-5p. Results: The results showed that LINC01534 was upregulated in both OA cartilage tissue and OA chondrocyte model. In addition, silencing LINC01534 significantly alleviated the inhibitory effect of IL-1β on expressions of aggrecan and collagen II in chondrocytes, and significantly downregulated the expression of matrix metalloproteinases in IL-1β-induced chondrocytes. Meanwhile, silencing LINC01534 also significantly inhibited the productions of proinflammatory factors NO, PGE2, TNF-α, IL-6, and IL-8 in the IL-1β-induced chondrocytes. Furthermore, miR-140-5p was confirmed to be a direct target of LINC01534. More importantly, inhibition of miR-140-5p significantly reversed the inhibitory effect of silencing LINC01534 on abnormal matrix degradation in the IL-1β-induced chondrocyte model of OA. Conclusion: Therefore, LINC01534 could promote the abnormal matrix degradation and inflammatory response of OA chondrocytes through the targeted binding of miR-140-5p.